The Intergenerational Persistence of Poverty in High-Income Countries - Zachary Parolin; Rafael Pintro Schmitt; Gøsta Esping-Andersen; Peter Fallesen (Institute of Labor Economics (IZA), 2023)
Exposure to childhood poverty increases the likelihood of adult poverty. However, past research offers conflicting accounts of cross-national variation in the strength of the intergenerational persistence of poverty and the mechanisms through which it is channeled. This study investigates differences in intergenerational poverty in the United States (U.S.), Australia, Denmark, Germany, and United Kingdom (UK) using administrative- and survey-based panel datasets. We introduce a framework to decompose intergenerational poverty into family background effects, mediation effects, tax/transfer insurance effects, and a residual poverty penalty. Intergenerational poverty in the U.S. is four times stronger than in Denmark and Germany, and twice as strong as in Australia and the UK. Intergenerational poverty in Denmark is primarily channeled through family background effects, but persists in the UK and Germany through mediators such as adult education and employment. The U.S. disadvantage is not channeled through family background, mediators, neighborhood effects, or racial/ethnic discrimination. Instead, the U.S. has comparatively weak tax/transfer insurance effects and a more severe residual poverty penalty. Should the U.S. adopt the tax/transfer insurance effects of peer countries, its intergenerational poverty persistence could decline by more than one-third. The study offers a foundation for renewed research on the intergenerational persistence of poverty in high-income countries.
Keywords: I32; I38; 330; poverty; intergenerational mobility; stratification; social mobility